Students’ Enrolment Patterns in Schools of a Telangana Town — A Sociological Analysis - Gosikonda, Sreeramulu (THE PRIMARY TEACHER, 2017)
The primary aim of a school is the socialisation of students. According to the Right of Children to Free and Compulsory Education (RTE) Act 2009, every child has the right to full–time free elementary education in a formal school. The Act further entails that 25 per cent of the seats in all private schools must be allotted to students belonging to Economically Weaker Section (EWS) families. In India, parents’ preference for English medium private schools shows their growing aspirations towards the education of their children. One State witnessing such a trend is Telangana. The State is witnessing a mushrooming of private schools. Moreover, the enrolment rate in English medium schools in the State is increasing, while it is decreasing in Telugu and Urdu medium schools. With this backdrop, an empirical study was conducted in Huzurabad town of Karimnagar district in Telangana. The study aims to understand the pattern of students’ enrolment in both government and private schools. This paper aims to find out the impact that social category and gender have on the schooling of children.